STRATEGI PEMASARAN UMKM - Tarmizi, Ahmad (Economic Faculty, Attahiriyah Islamic University, 2018)
This article is a summary of several journals that were rereviewed about the Micro, Small and Medium Enterprises (MSMEs) Marketing Strategy. MSMEs are one of the leading driving forces in economic development and play a significant role in the economy. Economic players such as the owners of MSMEs now not only can produce a product, but also must adapt and implement technological developments into their economic activities. So that the marketing strategies of MSME owners become complex and numerous. The purpose of this study is to identify marketing strategies in the development of MSMEs. The data obtained is from the literature studies of existing journals as secondary data. The results obtained show that there are two strategies in the marketing of MSMEs which become priority strategies, namely: (1) The owner of MSMEs applies e-commerce to become a market leader, (2) The owners of MSMEs provide branding to emerge brand image of their products. Keywords: E-commerce, Brand Image, Strategi Pemasaran, UMKM